PHP & MySQL Everyday Apps for Dummies - Valade, Janet (Wiley Publishing, 2011)
PHP and MySQL Everyday Apps For Dummies is a one-stop reference providing all you need to build dynamic, real-world, ready-to-use apps with the popular PHP (a scripting language) and MySQL (a database system) software. The book is a hands-on, go-to-guide that